Traversing Emotional Spaces: Social Media Affordances and Emotion Regulation in Times of Physical Isolation - Lulu Peng; Jinping Wang; Nanxiao Zheng; Xiaoping Guo (Social Media + Society, 2024)
People’s emotional life is increasingly interwoven with social media. Against the background of the COVID-19 pandemic and lockdown in China, this study investigated social media affordances enacted during people’s emotion regulation processes. By analyzing in-depth interviews with 27 Shanghai residents going through a 2-month lockdown, we identified intersections between social media affordances and different emotion regulation processes: selectivity and intrapersonal emotion regulation; visibility and emotional self-presentation; bandwidth and interpersonal emotion regulation; connectivity and collective emotion regulation. This study extended our knowledge of mediated emotion regulation processes and enriched our understanding of the dynamic relations between users, media technologies, and emotional and social contexts.